2001
DOI: 10.1093/jn/131.5.1427
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Suppressor Protein p53 mRNA and Subcellular Localization Are Altered by Changes in Cellular Copper in Human Hep G2 Cells

Abstract: Copper toxicity causes hepatic damage that can lead to the development of hepatocarcinoma. Similarly, copper deficiency has been reported to increase hepatocyte tumorigenesis. Thus, the objective of this work was to explore the role of copper toxicity and deficiency in the regulation of the tumor suppressor protein p53. Using Northern analysis, Western analysis, immunocytochemistry and the human hepatoma cell line Hep G2, this work showed that elevations in hepatocyte copper consistent with Wilson's disease (5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 36 publications
4
42
0
Order By: Relevance
“…The current study confirms previous works showing that various chemical compounds have the potential to up-regulate stress genes in human liver carcinoma (HepG 2 ) cells [26,29,30]. Exposure of HepG 2 cells to PCP revealed a significant induction of a number of stress genes including CYP1A1, XRE, HMTIIA, c-fos, and GADD153.…”
Section: Gene Profile Assaysupporting
confidence: 91%
See 1 more Smart Citation
“…The current study confirms previous works showing that various chemical compounds have the potential to up-regulate stress genes in human liver carcinoma (HepG 2 ) cells [26,29,30]. Exposure of HepG 2 cells to PCP revealed a significant induction of a number of stress genes including CYP1A1, XRE, HMTIIA, c-fos, and GADD153.…”
Section: Gene Profile Assaysupporting
confidence: 91%
“…Exposure of HepG 2 cells to PCP revealed a significant induction of a number of stress genes including CYP1A1, XRE, HMTIIA, c-fos, and GADD153. Further, several studies report that metal and nonmetal compounds modulate transcriptional activation of stress genes in the human hepatoma cell line, HepG 2 [26,29,30]. Moreover, several reports in the literature have addressed the potential of organochlorine pesticides to initiate reporter gene transcription from estrogen response elements in DNA [32].…”
Section: Gene Profile Assaymentioning
confidence: 99%
“…To resolve this issue, HMVEC tubulogenesis was initiated and the cells were exposed to three copper chelators: ammonium tetrathiomolybdate (TTM), tetraethylpentamine (TEPA), or bathocuproinedisulfonic acid (BCS). These chelators were chosen for their copper specificity and reported low toxicity in a number of cell types (10,26,27). Their low toxicity in HMVECs was confirmed by a trypan blue exclusion cell viability assay, which found no statistically significant decrease in viability from the use of any of the three chelators at the concentrations used in our experimental conditions.…”
Section: Resultsmentioning
confidence: 72%
“…Although the qualitative changes in CCS abundance under the copper altered conditions used in this study were consistently reproduced, differences in the absolute amount of CCS were observed (see Table 1). Because the cell number and media requirements were kept identical in each experiment, this variation in the absolute amount of CCS under such conditions likely reflects reported differences in the amounts of available copper for chelation in unique subcellular locations that may change during physiological events such as the cell cycle (31). Consistent with this concept, statistical analysis of the -fold differences in Table 1 illustrates that C244S,C246S CCS was the only mutation where the change in CCS abundance with copper content was statistically significant when compared with the endogenous CCS ϩ/ϩ cells.…”
Section: Discussionmentioning
confidence: 99%